Widespread distribution of resistance to triazole fungicides in Brazilian populations of the wheat blast pathogen - Poloni, Nadia Maria [UNESP]; Carvalho, Giselle [UNESP]; Nunes Campos Vicentini, Samara [UNESP]; Francis Dorigan, Adriano [UNESP]; Nunes Maciel, João Leodato; McDonald, Bruce A.; Intra Moreira, Silvino [UNESP]; Hawkins, Nichola; Fraaije, Bart A.; Kelly, Diane E.; Kelly, Steven L.; Ceresini, Paulo C. [UNESP] (Wiley, 2021)
Fungicides have not been effective in controlling the wheat blast disease in Brazil. An earlier analysis of 179 isolates of Pyricularia oryzae Triticum lineage (PoTl) sampled from wheat fields across six populations in central-southern Brazil during 2012 discovered a high level of resistance to strobilurin fungicides. Here we analysed azole resistance in the same strains based on EC50 measurements for tebuconazole and epoxiconazole. All six Brazilian populations of PoTl exhibited high resistance to both azoles, with in vitro EC50 values that were at least 35 to 50 times higher than the recommended field doses. We sequenced the CYP51A and CYP51B genes to determine if they were likely to play a role in the observed azole resistance. Although we found five distinct haplotypes in PoTl carrying four nonsynonymous substitutions in CYP51A, none of these substitutions were correlated with elevated EC50. CYP51B was sequenced for nine PoTl isolates, three each representing low, medium, and high tebuconazole EC50. Both PoTl CYP51A and CYP51B could complement yeast CYP51 function. All PoTl CYP51A-expressing yeast transformants were less sensitive to triazoles than the PoTl CYP51B ones. Transformants expressing PoTl CYP51A haplotype H1 carrying the R158K substitution were not more resistant than those expressing PoTl CYP51A haplotype H5, which is synonymous to haplotype H6, found in triazole-sensitive P. oryzae Oryza isolates from rice blast. Therefore, the reduced triazole sensitivity of wheat blast isolates compared to rice blast isolates appears to be associated with a non-target-site related resistance mechanism acquired after higher exposure to triazoles.
Keywords: CYP51A; CYP51B; epoxiconazole; Pyricularia oryzae Oryza lineage; Pyricularia oryzae Triticum lineage; tebuconazole